A Hybrid Acoustic-Wave Resonator and Lumped-Element Ladder Filter - Wagner, Michael; Gossmann, Timo; Tomasik, Jakob; Weigel, Robert; Hagelauer, Amelie Marietta; Leuschner, Stephan (IEEE International Ultrasonics Symposium, IUS, 2018)
RF frequency filters employing acoustic-wave resonators are used in common modern handsets for mobile communication. These resonators make use of the piezoelectric effect, i.e. their characteristics therefore strongly depend on employed materials and technology and comprise relatively fixed behavior. Classic filter design theory, however, is dealing with lumped reactive elements like inductors and capacitors for the realization of any-order filter designs instead. This theoretical treatment can lead to a multitude of realizable designs which makes it in fact very generous but also complex. Furthermore, theory is well-known and resulting structures are excessively explored in practice. In this paper, a new practical approach for the combination of these two filter types, preserving their respective benefits, is presented.
Created from Fastlane, Scopus look-up

Simulations of a New Design Concept for Hybrid Ladder Filters - Wagner, Michael; Gossmann, Timo; Tomasik, Jakob; Weigel, Robert; Hagelauer, Amelie Marietta (2019 IEEE 20th Wireless and Microwave Technology Conference, WAMICON 2019, 2019)
In this paper, a new concept from circuit design perspective is presented and evaluated based on simulations. The concept allows for manipulation of the fixed behavior and limited effective electromechanical coupling factor (k-eff^2) of acoustic-wave resonators by additional lumped-element resonators. This hybrid approach enables resonance spreading of single acoustic-wave resonators and can be used for wide-band filter designs. A theoretical description of the concept is given and its benefits and application to filter design are outlined. Important characteristics are illustrated by a design example.
CRIS-Team Scopus Importer:2019-08-06

Theoretical Derivation of Bandwidth Limits of a Symmetric Acoustic-Wave-Lumped-Element Resonator (AWLR) Module - Wagner, Michael; Leuschner, Stephan; Weigel, Robert; Hagelauer, Amelie Marietta (ANALOG 2018; 16th GMM/ITG-Symposium, 2018)
This paper focuses on theoretical investigations on "Acoustic-Wave-Lumped-Element Resonator" (AWLR) modules that have gained much interest in the last few years regarding general progress in radio frequency (RF) filter techniques and design. It is shown how the bandwidth characteristics depend on the electro-mechanical coupling factor of the employed piezoelectric material. General approximation formulas for the achievable 3 dB-bandwidth and for the maximum achievable bandwidth of symmetric AWLR modules are given. The results of the mathematical derivation are verified by simulation.<br